Participative Pricing Strategy - Rabbanee, Fazlul (2021)
Unlike the passive role that consumers usually play in conventional pricing mechanisms, participative pricing enables consumers to play an active role in setting the price for a product or service. Pay What You Want (PWYW) is a form of participative pricing strategy where consumers enjoy complete autonomy in setting the price they pay for a product including a price of ‘zero’. In this presentation, the author focuses on the taxonomy of participative pricing mechanism and summarizes the key findings of the papers that the author published on PWYW pricing in several top ranked journals during 2016-2021. The findings reveal that different economic (e.g., internal reference price, price consciousness), social (e.g., social desirability) psychographic (e.g., altruism, fairness perception), and situational (e.g., perceived crowding, time pressure) variables influence consumers’ PWYW pricing decision. The findings further shows mediating mechanisms and moderating influences of some of these variables on each other’s effects. Finally, the presentation highlights on the implications of these findings and relevant directions for future research.